Non-photochromic solar energy storage in carbon nitride surpassing blue radicals for hydrogen production. Issue 14 (7th March 2022) - Wu, Pei-Shan; Lin, Tzu-Jen; Hou, Sheng-Shu; Chen, Chih-Chia; Tsai, Dai-Ling; Huang, Kuan-Hsiang; Wu, Jih-Jen
Abstract : This study demonstrates nonphotochromic solar energy storage in the in-plan short-range-ordered KPHI, which photoelectron storage and catalytic activity surpass the blue radicals derived from conventional crystalline KPHIs. Abstract : Potassium poly(heptazine imide) (KPHI) exhibiting the dual functionality of photon absorption and photoelectron storage for solar energy conversion is a new class of ionic two-dimensional (2D) carbon nitrides. Rather than forming blue radicals upon storing photoelectrons in the yellow crystalline KPHIs, here non-photochromic solar energy storage in the in-plane short-range-ordered KPHI is reported, which demonstrates superior photocatalytic and dark photocatalytic activities for hydrogen evolution. Density functional theory calculations confirm that the electron storage capacity of the short-range-ordered KPHI is higher than that of the crystalline one. Moreover, the molecular structure remains unchanged after electrons are stored, resulting in non-photochromic solar energy storage in short-range-ordered KPHI. In crystalline KPHI, the stored photoelectrons drive the change of potassium ion locations to form a blue radical. This work demonstrates that the photophysical properties of light-storing carbon nitrides are tunable by modifying the microstructure of KPHIs towards efficient solar energy storage and conversion.